The Magic and Metaphysics of Shit: The Production of Space and Digital Technology. Issue 3 (1st October 2020) - Capener, David
Abstract : ABSTRACT Reading Henri Lefebvre alongside Bernard Stiegler, this paper explores the changes that have taken place to the production of space in our age of digital technology. Lefebvre sensed the radical changes taking place in society through the implementation of computational technologies. He asked a prescient question: How is this space being produced? Lefebvre was unable to foresee the significant changes to the actual mechanics of the production of space brought about by the third industrial revolution. A thinker who does do this is Bernard Stiegler who is interested in how new digital technologies change memory via tertiary mnemotechnical devices – memory storage devices that are external to the human body. Reading Lefebvre alongside Stiegler might seem unusual, however I will demonstrate that implicit in Lefebvre's argument regarding the production of space is memory and implicit in Stiegler's argument regarding the exteriorization of memory in technics is space.